2020
DOI: 10.3171/2020.8.focus20571
|View full text |Cite
|
Sign up to set email alerts
|

Malpractice and socioeconomic aspects in neurosurgery: a developing-country reality

Abstract: OBJECTIVENeurosurgery occupies a prominent place in medical malpractice, but cases are still underreported in Brazil. This study describes the socioeconomic issues of medical malpractice in neurosurgery procedures and how they culminate in unfavorable outcomes in a developing country.METHODSThe authors analyzed 112 neurosurgical procedures listed in the Brazilian Hospital Information System (Sistema de Informações Hospitalares do Sistema Único de Saúde [SIHSUS]) records in the DATASUS (Departamento de Informát… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 28 publications
0
2
0
1
Order By: Relevance
“…[1] CPGs do not decrease the incidence of malpractice suits or costs Spine surgery predominates in number of malpractice suits in neurosurgery, comprising 40% of them. [2] According to our results on CPGs' attitudinal behaviors, spine surgeons do not regard adherence to guidelines as a factor associated with the decreasing likelihood of malpractice suits -in both CPG user and non-CPG user groups [Table 2]. In our study, we found that most spine surgeons disagreed that following CPGs help to reduce costs (n = 125/304, 44.07).…”
Section: Discussionmentioning
confidence: 61%
“…[1] CPGs do not decrease the incidence of malpractice suits or costs Spine surgery predominates in number of malpractice suits in neurosurgery, comprising 40% of them. [2] According to our results on CPGs' attitudinal behaviors, spine surgeons do not regard adherence to guidelines as a factor associated with the decreasing likelihood of malpractice suits -in both CPG user and non-CPG user groups [Table 2]. In our study, we found that most spine surgeons disagreed that following CPGs help to reduce costs (n = 125/304, 44.07).…”
Section: Discussionmentioning
confidence: 61%
“…Özellikle gelişmekte olan ülkelerde tıbbi malpraktis olgu sayısının gelişmiş ülkelere nazaran daha düşük düzeylerde olmasının sosyoekonomik eşitsizlik ve toplumun hakları konusunda düşük farkındalığı olabileceği ifade edilmiştir. 35 Çalışmamızda da tıbbi malpraktis iddia ve olgu sayıları, ülkelerin ekonomik, eğitim ve sağlık boyutlarıyla kalkınmışlığını değerlendiren HDI ile güçlü derecede, hukuk sistemlerinin gelişmişliğini gösteren hukukun üstünlüğü endeksi ile de çok güçlü derecede korele bulunmuştur (Tablo 1). Bir ülke sosyal, hukuksal ve ekonomik olarak geliştikçe, daha iyi bir sağlık hizmeti sunulabilecek ve tıbbi süreçlerdeki hata oranları azalacaktır.…”
Section: Discussionunclassified
“…Population disparities among regions on the basis of socioeconomic background compound issues resulting from access to and affordability of neurosurgical care related to the COVID-19 pandemic. 1 , 32 Altered protocols to combat the dissemination of the virus and treat patients with COVID-19 may be particularly harmful to neurosurgical patients in regions with limited access to the health care system, leaving patients to die without proper resources to provide comprehensive care. 16 , 33 The Southeast region has a high-volume regional medical center, in which 47.4% of total costs involved neurosurgery procedures in Brazil in 2020.…”
Section: Discussionmentioning
confidence: 99%